Modernistyczny budynek jednorodzinny w makrownętrzu cieku wodnego = Modern family house in ecological macro-structure of watercourse - Greinert, Lidia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Increased urban pressure in the end of the twentieth and early twenty-first century meant, that for building purposes shall be allocated areas managed so far as natural ones. In relation to some of them, the arguments fall about devastation of environment by the building forms. Current building trends are including the nature as an important regulatory factor.
Keywords: zabudowa jednorodzinna; modernizm w architekturze; family housing; modern architecture